Medicine : the definitive illustrated history - Parker, Steve, 1952-; Black, Alexandra (New York, New York : DK Publishing, 2016)
"Medicine tells the fascinating story of the discipline, from ancient times to the present day, charting developments in healing, diagnosis, surgery, and drugs in a vividly visual and accessible format. Follow the gory pitfalls and the miraculous breakthroughs of medical history from trepanning, bloodletting, and body snatching to the latest developments in IVF and gene therapy. Clear diagrams explain major diseases, such as cancer, and enhance understanding of human anatomy, surgical instruments, and the progression of treatment over the centuries, setting the great milestones of medical history in their wider social context. A complementary illustrated reference section profiles all the main body systems and organs and explains their relevance in terms of the advancement of medicine. Follow the gory pitfalls and the miraculous breakthroughs of medical history from trepanning, bloodletting, and body snatching to the latest developments in IVF and gene therapy. Clear diagrams explain major diseases, such as cancer, and enhance understanding of human anatomy, surgical instruments, and the progression of treatment over the centuries, setting the great milestones of medical history in their wider social context. A complementary illustrated reference section profiles all the main body systems and organs and explains their relevance in terms of the advancement of medicine. A compelling blend of riveting stories, accessible information, and striking illustrations, Medicine shows and tells how medicine has evolved into the lifesaving discipline it is today,"--
Ancient wisdom to 700 -- Revival and Renaisssance 700-1800 -- Science takes charge 1800-1900 -- Era of specialization 1900-1960 -- Promises old and new 1960-present
Contributors: Alexandra Black, Philip Parker, Sally Regan, Marcus Weeks.
Includes bibliographical references and index.
Keywords: History of Medicine; Medicine History Pictorial works